HB-EGF Activates the EGFR/HIF-1α Pathway to Induce Proliferation of Arsenic-Transformed Cells and Tumor Growth - Wang, Lin; Lu, Yi-Fan; Wang, Chao-Shan; Xie, Yun-Xia; Zhao, Yan-Qiu; Qian, Ying-Chen; Liu, Wei-Tao; Wang, Min; Jiang, Bing-Hua (Frontiers in Oncology, 2020)
Arsenic was recently identified as a pollutant that is a major cause of lung cancer. Since heparin-binding EGF-like growth factor (HB-EGF) was reported to be a promising therapeutic target for lung cancer, we investigated the role and mechanism of HB-EGF during arsenic-induced carcinogenesis and development of lung cancer. HB-EGF expression were upregulated in As-T cells, lung cancer cell lines, and in most lung cancer tissue samples; and HB-EGF activated the EGFR/ p-ERK/HIF-1α pathway and induced VEGF by regulating HIF-1α transcription. HIF-1α transcriptional stimulation by HB-EGF was facilitated by PKM2 and played an important role in HB-EGF’s effect on cells. An HB-EGF inhibitor(CRM197, cross-reacting material 197) slowed cell proliferation and inhibited migration of As-T and A549 cells, and inhibited tumor growth. PKM2 also played an important role in the proliferation and migration in As-T cells. The positive staining ratios of EGFR phosphorylation (Y1068) and PKM2 were significantly higher in most cases of lung cancer than in paired normal tumor-adjacent lung tissues; and HB-EGF expression levels strongly correlated with p-EGFR expression levels. Thus, HB-EGF drives arsenic-induced carcinogenesis, tumor growth, and lung cancer development via the EGFR/PKM2/HIF-1α pathway.